"Voltage-Current Ratio Difference" Concept for identifying the dominant harmonic source. (October 2020) - Safargholi, Farhad; Malekian, Kaveh; Schufft, Wolfgang
Highlights: An invasive concept for identifying the harmonic dominant side is proposed. This concept does not require the equivalent harmonic impedances (or admittances). The proposed concept is based on the variation of the "voltage current ratios". The desired variation can be reached by installation of a known serial impedance. Abstract: This paper proposes a new concept for identifying the harmonic dominant side. The proposed concept is named as "voltage-current ratio difference" for determining the dominant equivalent harmonic voltage source and "current-voltage ratio difference" for determining the dominant equivalent harmonic current source. In contrast to most previous methods, the proposed concept does not require the equivalent harmonic impedance (or admittance) of the utility and customer sides as input data. Indeed, this concept requires the measured harmonic voltage as well as current at the point of common coupling in two states: in normal operation and in operation with the installation of a known serial impedance (or parallel admittance) between the utility and customer. The methodology and application of this concept are thoroughly presented in this paper. In addition, some practical issues about the implementation of the concept are discussed. In this regard, requirements for the serial impedance (or parallel admittance) at the fundamental frequency and at each harmonic order are defined to yield reliable results.